The importance of suppliers selection towards sucessful procurement in Petronas Gas Berhad (PGB) / Faranadia Zakbah - Zakbah, Faranadia (Faculty of Business and Management, 2007)
Problem Statement - For the past few years, PGB has failed to meet the importance standard in procurement. Apart of economic condition, the problem comes from the suppliers itself. This make PGB not only loss of revenue but also loss of business opportunity. This research has two objectives. Research Objective- a) To identify the relationship between suppliers' criteria and successful procurement and b) To determine factors contributes to the success of procurement. Methodology - Descriptive Research and probability sampling has been conducted in this study. A total numbers of 70 employees from Procurement Department at Peninsular Malaysia are selected as respondents and questionnaire has been delivered to all of them in order to gain information about PGB suppliers. Findings - At the end of this research, it give a better description on which factor of suppliers criteria that impact the most on PGB performance especially in procurement department. In addition, several recommendations have been proposed in order to overcome the problem. Overall, this research provides evidence to support procurement and supply chain management in handling suppliers. It is recommended that further research be undertaken to test the validity and improve this research because changes in environmental will change suppliers selection criteria.